2014
DOI: 10.1002/ejlt.201400082
|View full text |Cite
|
Sign up to set email alerts
|

Oil composition in stored walnut cultivars—quality and nutritional value

Abstract: The effects of temperature and O2 availability on quality attributes and nutritional value of oil in four walnut (Juglans regia L.) cultivars (Chandler, Hartley, Franquette, and Ioli) were investigated. Dried kernels, all of initial high quality, were packaged under air or N2 or CO2 and stored at 1 °C or 20 °C for 12 months. Results showed that the saturated fatty acids (SFA) myristic, palmitic, stearic, and arachidic remained stable during storage, whereas the unsaturated palmitoleic, oleic (OL), gondoic, lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 32 publications
(76 reference statements)
11
36
1
Order By: Relevance
“…Although the kernel moisture could vary as a function of season, harvest time and environmental conditions, both wild accessions and commercial cultivars had the same moisture content of about 3.5% (w/w) (data not shown) after drying, suitable for long storage . This value was in agreement with those reported by Amaral et al and Pereira et al and lower than those reported in other studies …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Although the kernel moisture could vary as a function of season, harvest time and environmental conditions, both wild accessions and commercial cultivars had the same moisture content of about 3.5% (w/w) (data not shown) after drying, suitable for long storage . This value was in agreement with those reported by Amaral et al and Pereira et al and lower than those reported in other studies …”
Section: Resultssupporting
confidence: 94%
“…Commercial varieties generally showed a higher mean oil content than wild genotypes, but the difference was quite small (∼4% w/w) (Table ). The oil content of the commercial varieties was comparable to the literature data for the same cultivars . However, there were some differences between commercial varieties.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Consumers also feel convinced that nuts in the husk are fresh and were harvested in the same year. An argument supporting the consumption of unripe hazelnuts sold in the husk is their higher content of polyphenols and some fatty acids, as well as better palatability (Ebrahem et al 1994;Farinelli et al 2001;Ciemniewska-Żytkiewicz et al 2015). The higher water content, reflected in higher weight, with 41% share of the husk, is an advantage, important for producers (Ebrahem et al 1994;Zdyb 2012;Ciemniewska-Żytkiewicz et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The results of numerous experiments on the storage of different kinds of ripe nuts suggest that controlled and modified atmosphere, aside from having a positive effect on the sensory features and chemical composition, can reduce nut weight losses, thus enabling longer storage (Maté et al 1996;Maskan & Karataş 1998;Mexis et al 2009;Christopoulos & Tsantili 2011;Ghirardello et al 2014, Christopoulos & Tsantili 2015.…”
Section: Introductionmentioning
confidence: 99%